European urban freight transport policies and research funding: are priorities and H2020 calls aligned? - Lozzi, Giacomo; Gatta, Valerio; Marcucci, Edoardo (REGION, 2018)
The European Commission (EC) has recently developed a growing awareness and interest with respect to the challenges urban freight transport (UFT) poses. Consequently, the EC has started defining specific policies and promoted dedicated tools to address them. Transport is a shared responsibility between the EU and the Member States, where the subsidiarity principle applies. Accordingly, the EC provides European local authorities with support in the different areas, including research and innovation funding. This paper aims to assess the linkage and consistency between EC policy priorities for UFT and the corresponding calls of the new Horizon 2020 (H2020) Research Programme, created by the EC in order to foster research and innovation. The paper identifies and extrapolates in a comparable format 10 UFT priority solutions, and consequently estimates their degree of correspondence with the H2020 Work Programmes (WPs) on the basis of the weight in monetary terms resulting from the research funds allocated to each of them. Findings show that, generally, the EC addresses UFT through a systematic and coherent approach. Moreover, all the identified solutions are covered by at least one H2020 call, although the extent of the coverage is heterogeneous.